Prevention of Low Back Pain in Adults with a Back School-Based Intervention - Pablo Hernandez-Lucas (MDPI AG, 2021)
Background: Low back pain is highly prevalent and has a major socio-economic impact worldwide. Among the rehabilitation options is the Back School, which consists of programmes that include exercise and educational interventions to treat and prevent back pain. The effects of this type of programme are usually evaluated in patients with low back pain. The aim of this study was to evaluate the effects on low back functionality and the prevention of medical visits due to low back pain during one year of follow-up in a healthy adult population. Methods: A quasi-experimental study was conducted with 56 healthy participants who were divided into an experimental group (n = 30), who underwent the programme consisting of a total of 16 sessions, and a control group (n = 26), who did not undergo the intervention. All participants were administered the Partial Curl-up Test, Biering Sorense Test, Modified Schöber Test, and Toe Touch Test, and they completed the Short Form 36 Health Survey before and after the intervention. In addition, a telephone call was made to ask whether they attended a doctor for low back pain in the following year post-intervention. Results: In the experimental group, statistically significant improvements were observed in trunk muscle strength, spinal flexion joint range of motion, and hamstring flexibility, and they had fewer visits to the doctor for low back pain in the following year. Conclusions: The theoretical–practical programme based on the Back School seems to have beneficial effects on low back functionality by increasing its strength and flexibility in an adult population. In addition, this programme reduced the number of medical visits due to low back pain during the following year after the intervention.